Lived Experiences of Mothers with Attention-Deficit/Hyperactive Children: A Phenomenological Approach - Reza Abbasalizadeh Ranjbari; Rahim Badri; khalil Esmailpour; Ali Nagi Agdasi (Journal of Qualitative Research in Health Sciences, 2022)
Background: This study aimed to investigate the lived experiences of mothers with attention-deficit/ hyperactive children.Methods: The present qualitative descriptive study was conducted based on a phenomenological approach that investigated the experiences of primary caregivers of attention-deficit/ hyperactive children. The population of the study included mothers of attention-deficit/hyperactive primary school students in Tabriz. A total of 13 children were selected using purposive sampling. Data were collected through face-to-face, in-depth, and semi-structured interviews with participants. The interviews were conducted in schools and the Hasti Counseling Center. Moreover, Smith’s cognitive phenomenological method was used to analyze the data.Results: The analysis of the data revealed 4 main themes and 25 subthemes including emotional responses (depression, loneliness, anger and rage, embarrassment, desire to have a calm child, stress, confusion, remorse, regret, frustration, anxiety and dread), behavioral responses (self-blame, frequent crying, shouting, aggression, trying to control oneself), physical responses (palpitation, feeling hot water drops on one’s head), and cognitive responses (feeling inhuman, isolation, feeling guilty, embarrassed, and blameful, problems in pregnancy, insanity, feeling hyperactive due to inability to control oneself, feeling accused of lying).Conclusion: The results of this study will pave the way for further research in the field of mental health interventions for mothers of attention-deficit/hyperactive children. Accordingly, it is essential to design and evaluate the effectiveness of psychotherapy interventions that can cover various dimensions of the problems of this group of mothers.